2015
DOI: 10.1007/s00198-015-3077-2
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thinning and progressive cortical porosity in female patients with systemic lupus erythematosus on long-term glucocorticoids: a 2-year case-control study

Abstract: Longitudinal microstructural deterioration in SLE is characterized by cortical thinning and increased cortical porosity. Cortical bone is an important source of bone loss in SLE patients on glucocorticoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…HR‐pQCT was also used to characterize changes in bone architecture in women with systemic lupus erythematosus treated long‐term with glucocorticoids. Cortical thinning and increased cortical porosity were the features of longitudinal microstructural deterioration in treated individuals …”
Section: Bone Quality Changes In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…HR‐pQCT was also used to characterize changes in bone architecture in women with systemic lupus erythematosus treated long‐term with glucocorticoids. Cortical thinning and increased cortical porosity were the features of longitudinal microstructural deterioration in treated individuals …”
Section: Bone Quality Changes In Diseasementioning
confidence: 99%
“…Cortical thinning and increased cortical porosity were the features of longitudinal microstructural deterioration in treated individuals. 62 In addition to lupus and rheumatoid arthritis, asthma, and other conditions in which glucocorticoids are used for extended periods, fracture risk is increased in individuals with COPD taking inhaled steroids. While life-style features leading to COPD also affect bone turnover and fracture risk, 63 there is a single study 64 comparing bone quality in newly formed and older bone of individuals with COPD who did and did not sustain fragility fractures on the basis of Raman spectroscopy.…”
Section: Secondary Osteoporosismentioning
confidence: 99%
“…Interestingly, also in SLE patients, it is the cortical bone that is predominantly affected. 21 However, there are also studies showing a trabecular bone loss in SLE patients, 23 but these effects are not as prominent as the cortical effects and it remains unclear how much of the trabecular phenotype is due to the glucocorticoid treatment in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution peripheral quantitative computed tomography (HR-pQCT) is an emerging method for the assessment of bone microarchitecture, geometry and bone strength. A limited number of studies using HR-pQCT as imaging modality in SLE were published and demonstrated reduced bone strength in patients with SLE (both in patients on long-term GC therapy and in patients not using GCs) compared to healthy controls [ 64 , 65 ]. HR-pQCT might be a better modality for the prediction of fracture risk in patients with SLE than DXA.…”
Section: Relationship Between Bone Mineral Density and Fractures In Smentioning
confidence: 99%